O Assentamento Olho D’água I: um Estudo de Caso sobre o impacto da dendeicultura em áreas de Assentamento na Amazônia Oriental - FILGUEIRAS, Tainara Carvalho Garcia Miranda (2024)
The research aims to analyze how oil palm cultivation has engendered changes in the use and occupation of the territory in areas of agrarian reform, from the “integration” of settled families to palm oil agribusiness. For such an approach to the problem, qualitative research with methodological support of a case study was chosen. In collecting data from a secondary source, bibliographical and documentary research was used. Primary data were collected through fieldwork, semi-structured interviews, and direct observation. The research results showed that the Olho D'Água I settlement experienced the phenomenon of oil palm cultivation and, as a consequence, suffered from changes in the dynamics of its agrarian space. This phenomenon results in social, psychological, and environmental impacts. The exchange of subsistence crops for oil palm cultivation led to changes in the way of life of these farmers who went from peasants to capital workers. Partnership contracts, despite having high risks to the demand for cultivation, were the only alternative for the survival of these families. Given this, it is possible to verify the trivialization of human needs, which contributes to the social vulnerability of peasants, with a greater need for the preservation and construction of public policies that enable a dignified life for this social group.